Business survival and market performance through Lean Six Sigma in the chemical manufacturing industry. Issue 2 (29th May 2019) - Muganyi, Peter; Madanhire, Ignatio; Mbohwa, Charles
Abstract : Purpose: The research paper aims to unveil the practical use of Lean Six Sigma and its effectiveness as a business survival strategic tool by a chemical product realization concern, as well as to establish the market and business performance impacts on the manufacturing entity. Design/methodology/approach: A case study approach was pursued with a multi-national chemical manufacturing entity in South Africa. A comprehensive literature research was undertaken to establish the contemporary tools used for implementing Lean Six Sigma, and the classification and flow of tools and steps undertaken to ensure the successful and effective application of Lean Six Sigma in a manufacturing organization and the benefits derived. The critical success factors and reasons of ineffective use of tools are reviewed. To ensure that a comprehensive research was conducted which is relevant to the body of knowledge in engineering, recent articles on the application of Lean Six Sigma were selected and reviewed during the progress of the study to add impetus to the relevance of the findings. Findings: The research findings were mainly based on the inferences obtained from a chemical product manufacturing concern in South Africa, to distinguish the efficacy and relevance of Lean Six Sigma as strategic business survival tool and imputing strategic resonance to corporate strategy. Research limitations/implications: This research was limited to distinguishing Lean Six Sigma as a business survival strategic tool and an ultimate enhancer of market performance for a chemical product manufacturing entity. The implementation and evaluation of the Lean Six Sigma methodology as a business survival strategic and market performance enhancement option for the case study organization was entailed as the corollary of deductive resemblance to similar entities. Practical implications: This study enables continuous improvement practitioners to evaluate the Lean and Six Sigma practices. The advantages posed by the simultaneous and optimized application of the two approaches versus individual application were assessed and verified to produce enhanced continuous improvement. This poses further challenges to scholars and academics to pursue further researches on the practicality of applying Lean Six Sigma as a strategic option. Originality/value: The paper prompts the efficacy of well publicized methodologies and evaluates their implementation for strategic performance for manufacturing organizations. The practical application, constraints and resultant effects of deploying Lean Six Sigma were reviewed to give impetus to the methodology.